2015
DOI: 10.1055/s-0034-1398576
|View full text |Cite
|
Sign up to set email alerts
|

Ground Reaction Force and Cadence during Stationary Running Sprint in Water and on Land

Abstract: This study was aimed at analyzing the cadence (Cadmax) and the peak vertical ground reaction force (Fymax) during stationary running sprint on dry land and at hip and chest level of water immersion. We hypothesized that both Fymax and Cadmax depend on the level of immersion and that differences in Cadmax between immersions do not affect Fymax during stationary sprint. 32 subjects performed the exercise at maximum cadence at each immersion level and data were collected with force plates. The results show that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The magnitude of these reductions is further reinforced by the large effect sizes observed between the environments in all variables and cadences (Fz peak = 4.08 to 5.21, impulse = 6.41 to 7.95, LR = 1.55 to 2.07). These findings corroborate those of other studies that also observed substantial reductions in the Fz peak when both environments were compared [11,13,17,19,24,25]. Alberton et al [13] found reductions in the order of 60 to 67% in Fz peak at 80 b min −1 , 100 b min −1 , and maximal effort in women with obesity, but no data is available on impulse or LR.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The magnitude of these reductions is further reinforced by the large effect sizes observed between the environments in all variables and cadences (Fz peak = 4.08 to 5.21, impulse = 6.41 to 7.95, LR = 1.55 to 2.07). These findings corroborate those of other studies that also observed substantial reductions in the Fz peak when both environments were compared [11,13,17,19,24,25]. Alberton et al [13] found reductions in the order of 60 to 67% in Fz peak at 80 b min −1 , 100 b min −1 , and maximal effort in women with obesity, but no data is available on impulse or LR.…”
Section: Discussionsupporting
confidence: 85%
“…Alberton et al [13] found reductions in the order of 60 to 67% in Fz peak at 80 b min −1 , 100 b min −1 , and maximal effort in women with obesity, but no data is available on impulse or LR. In eutrophic young adults, the magnitude of reduction in Fz peak during the stationary running exercise is typically somewhere between 40-58% at different submaximal intensities [11,17,24,25], whereas the impulse and LR were found to be 67.5-68.6% [11,24] and 20.6-38.6% [17] lower in the aquatic environment, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In order to evaluate the ground reaction force (GRF) in the aquatic environment, studies have been developed over the last two and a half decades (Alberton et al, 2013(Alberton et al, , 2014(Alberton et al, , 2015Barela & Duarte, 2008;Barela, Stolf, & Duarte, 2006;Colado et al, 2010;de Brito Fontana et al, 2012;de Brito Fontana et al, 2015;Harrison et al, 1992;Haupenthal et al, 2013;Haupenthal, Ruschel, Hubert, de Brito Fontana, & Roesler, 2010;Miyoshi, Shirota, Yamamoto, Nakazawa, & Akai, 2004;Nakazawa, Yano, & Miyashita, 1994;Roesler, Haupenthal, Schutz, & de Souza, 2006;Triplett et al, 2009) analysing their three components: vertical (Fz), anterior-posterior (Fy) and mediolateral (Fx). The results of these studies have shown that the aquatic environment changes the magnitude and shape of the force-time curve for the three GRF components in comparison to dry land (Miyoshi et al, 2004;Roesler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%